Evaluación De La Calidad En La Atención Del Parto En Un Hospital Comunitario De Tabasco México, 2016 - Gutiérrez, Leticia Pérez; Gomez, Sergio Quiroz; Moreno, Marisol Guzmán (European Scientific Journal, ESJ, 2018)
Evaluating quality in health organizations is a great challenge. However, achieving this contributes to the health of the vulnerable population, such as the group of pregnant mothers. This research is descriptive, mixed and cross-sectional, which aims to assess the quality of care delivery in the Community Hospital of Tenosique, Tabasco. The population to be studied was the total number of physicians who work in the said hospital and who participated in the delivery of eutocic birth during 2016. For the development of this research, the program to evaluate obstetrics, gynecology, and neonatology services of Chile 2013 was taken as a reference. Criteria and standards were adapted by means of analysis of standards and official clinical practice guidelines of delivery care in Mexico. It was considered a theoretical basis for the evaluation of the quality according to the applications of Avedis Donabedian. As a result, a quality management evaluation instrument was obtained in childbirth care with three dimensions: Structure, Process, and Outcome. After applying the instrument, we can conclude that although sufficient quality was achieved in the dimensions of structure and process, inequities were identified in terms of availability and accessibility of material and human resources. Based on the quality of attention given to users, critical points were identified in favor of positive emotional environment, understanding, and approval of procedures.